Root Cause Analysis and Prevalence of Pressure Injuries a Neurointensive Care Unit - Hatice Esen; Cem Özbek (Galenos Yayinevi, 2023)
Objective:This study determined the prevalence and causes of the pressure injuries (PIs) in patients hospitalized our neurology intensive care unit (NICU).Materials and Methods:Planned as a cross-sectional, descriptive design, this study was conducted in training and research hospital NICU. The population of the study consisted of 338 patients. We retrospectively collected data from the hospital information management system that included the study period from January 1, 2020 to December 31, 2020.Results:Most 338 patients (54.4%) were male, the mean age of the patients was 68.44±15.5. Most patients were found to have comorbidities that may have contributed to the development of the PIs. The prevalence of the PI first appeared to be 15.4%, but since the PIs of 11 patients were found to have developed before admission to the NICU, yet with no stage progression, the prevalence of the PI was finally specified as 12.1% (n=41).Conclusion:It is of great importance to note that since the patients in the NICUs are at high risk of the PIs, close follow-up is accordingly necessary in terms of the PIs until discharge, it is necessary that nurses be informed as regard current guidelines to ensure offering appropriate nursing care.